P50 A local assessment of the escalating impact of pulmonary nodule surveillance and its relationship to patient outcomes in a DGH. (14th November 2013) - Calvert, LD; Chatterji, S; Miller, F; Brij, SO; Nakas, A
Abstract : Introduction: Recent national emphasis on increased awareness to improve detection of early lung cancer has led to dramatic increases in CT chest scans being performed. Consequently, increased detection of incidental lung nodules requires monitoring. In response, we set up a dedicated Nodule Surveillance Service (2 physicians, 1 radiologist, 1 surgeon, 1 tracker). To determine likely future service requirements, we assessed current resource allocation to nodule surveillance and related this to patient outcomes. Methods: Patients discussed though our local Nodule Surveillance Service over 6 months were identified, and their electronic records reviewed. Results: 107 patients (64 male) undergoing surveillance were discussed November 2012-May 2013: 71 had single nodules, 36 multiple. This constituted an average 25 extra patient-discussions/month. Mean age 67years (range 39–93years); smoking status 27 current, 53 ex-smokers, 22 non-smokers. Referral pathways: 2WW 37, inpatients 15, angiograms 6, PE service 5, respiratory OPD 17, other MDT 4, OPD 11, GP 3. Only 4/107 patients (3.7%) had high suspicion for lung cancer at outset, - 2 confirmed at surgery, 1 received radiotherapy (age 91yrs), 1 declined treatment. No further pathology was detected from surveillance. So far, a total of 246 CTs have been performed with 72 awaited (table 1 ). Fifteen patients had PET-CT (all low SUV). Fourteen underwent bronchoscopy (normal). Two had CT biopsy (benign), 2 declined biopsy, 2 were smaller at biopsy. One benign lesion was resected (patient choice). Only 28 patients have been discharged from surveillance; 10/28 resolved on 3month CT, 3/28 resolved on 6month CT, 15/28 stable on 12month CT. Fleischner guidance was accurately followed in 67%, most deviance due to delayed timing of 6month CT. Twenty-nine (27%) were discussed without documented nodule size. Conclusion: Nodule surveillance has put a significant burden on local Thoracic-Oncology services. No unexpected pathology was encountered during this surveillance period. Until clear clinical and/or radiological identifying factors for high risk patients are understood and rationalised, nodule surveillance will have to continue. There are cost implications not only for Radiology and Respiratory services, but also to patients' emotional and physical well-being. This highlights the continued need for clear surveillance protocols supported by service development.